1997
DOI: 10.1113/expphysiol.1997.sp004072
|View full text |Cite
|
Sign up to set email alerts
|

Parotid secretion daily patterns and measurement with ultrasonic flow probes in conscious sheep

Abstract: SUMMARYFive sheep under halothane anesthesia were prepared with bilateral transit time ultrasonic flow probes around the parotid ducts. The ducts were fitted with non-obstructive sampling catheters through their oral ends. After probe encapsulation (8 days), salivary flows were continuously recorded (4-5 days, dual-channel ultrasonic flowmeter). For rumination, eating, resting and drinking periods, respectively, the parotid daily outputs recorded were 1 96 + 0 57, 0 97 + 0 34, 2 84 + 0 41 and < 004 1 and bilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The example of the oribi indicates that a comparison of the different convergent evolutionary adaptations with respect to detailed foraging behavior might further elucidate the respective adaptive potential of the different morphophysiological features. Further studies on the digestive physiology of wild ruminants, e.g., comparing saliva or rumen fluid consistency, or saliva flow in conscious animals using flow probe implants (Meot et al, 1997) would shed further light on the hypotheses presented here. Additionally, we want to emphasize that until more controlled studies are performed using fistulated animals, the original concept of a functional reticular groove should not be completely dismissed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The example of the oribi indicates that a comparison of the different convergent evolutionary adaptations with respect to detailed foraging behavior might further elucidate the respective adaptive potential of the different morphophysiological features. Further studies on the digestive physiology of wild ruminants, e.g., comparing saliva or rumen fluid consistency, or saliva flow in conscious animals using flow probe implants (Meot et al, 1997) would shed further light on the hypotheses presented here. Additionally, we want to emphasize that until more controlled studies are performed using fistulated animals, the original concept of a functional reticular groove should not be completely dismissed.…”
Section: Discussionmentioning
confidence: 98%
“…A comparative evaluation of this hypothesis is lacking, but data collated by Van Soest (1982, Table 20.6) suggest that African buffalo (Syncerus caffer), for example, ruminate more in relation to food intake than giraffe (Giraffa camelopardalis); Dulphy et al (1995) found, in their review of more than 20 direct comparisons of sheep (grazer) and goats (mixed feeders), less ingestive and more rumination behavior in the sheep. As salivary flow might tend to be higher during rumination than during ingestion (Meot et al, 1997), this difference might be an additional reason for a higher salivary flow and rumen fluid throughput in grazers. And in theory, different requirements for saliva composition related to ingestion or rumination might additionally influence saliva composition, production, and ultimately salivary gland morphology between the feeding types.…”
Section: Functional Significancementioning
confidence: 96%
“…For example, parotid glands in ruminants secrete continuously during resting, eating and rumination, whereas submandibular glands increase their output volume during feeding [28]. Likewise the secretion rate, the composition of glandular secretions depends on whether the animal is resting, eating or ruminating [29] as well as on the nature of the diet consumed and the time spent feeding [28].…”
mentioning
confidence: 97%
“…Cattle with higher salivary flow rates would also appear desirable in terms of their capacity to buffer high-energy rations used in modern production systems. Consistent selection criteria could be followed under standardised conditions in animals with flow probe implants (Meot et al, 1997 …”
Section: Consequencesmentioning
confidence: 99%